Analysis of the Influence of Wind, Rainfall, and Sea Surface Temperature on Handline Catch Yields at Bungus Ocean Fishing Port - lestari, dewi joni lestari; Lisna; Heltria , Septy (Universitas Airlangga, 2025)
West Sumatra is one of Indonesia's Fisheries Management Areas with significant tuna potential, particularly yellowfin tuna (Thunnus albacares) and bigeye tuna (Thunnus obesus). This study aims to examine the influence of wind speed, rainfall, and sea surface temperature (SST) on handline catch yields at Bungus Ocean Fishing Port, West Sumatra, during the 2019–2023 observation period. The methodology employed a survey approach using secondary data obtained from https://data.marine.copernicus.eu/ the Meteorological Station of the Meteorology, Climatology, and Geophysics Agency (BMKG), and catch data from Bungus Ocean Fishing Port logbooks.The results indicate that the highest wind speed variability occurred during the 2019 East Monsoon Season, ranging from 8.80–11.10 m/s (25%) with a northwest direction, while the lowest wind speed was recorded during the 2021 Transitional Season 0.50–2.10 m/s, northerly (4%). The highest rainfall (552 mm/hari) occurred during the 2022 Transitional Season 2, while the lowest (30 mm/hari) was observed in 2019 during Transitional Season 2. The highest SST (30.31°C) was recorded during Transitional Season 1, and the lowest (27.19°C) during Transitional Season 2. The peak catch (451,201 tons) occurred during the 2019 west monsoon, whereas the lowest yield (20,359 tons) was recorded in 2023 during Transitional Season 2. Multiple linear regression analysis revealed that wind speed, rainfall, and SST collectively explained 25.2% of the variation in tuna catches, though their influence was not statistically significant. Correlation analysis further demonstrated no strong interdependence among wind speed, rainfall, and SST variables, factors outside the investigated variables accounted for 74.8% of the variance.